Agranulocytosis Induced by Antithyroid Drug (Propiltyourasil): A Rare Case - Ferdiana , Asihanti; Nyoman Satvika Dharma Yudha; Laksmi Sasiarini; Rulli Rosandi; Rinadhi Reza Bramantya (Universitas Brawijaya, 2025)
Antithyroid drugs can cause agranulocytosis in 0.2-0.5% of cases of Graves' disease, which can be life-threatening. Although rare, prompt management is crucial for a good outcome. A 41-year-old woman presented to the emergency department in March 2023 with complaints of fever, odynophagia, cough, nausea, vomiting, and weight loss. She had been diagnosed with hyperthyroidism in 2015 and was prescribed thiamazole 5mg once daily. She was declared cured in 2018. In February 2023, she was hospitalized for heart failure and diagnosed with Graves' disease. She was discharged with PTU 100mg three times daily. After two weeks of PTU treatment, the patient developed symptoms of agranulocytosis. Laboratory tests showed low white blood cell count and abnormal thyroid function. PTU therapy was discontinued, and the patient was treated with SC GCSF 300mg once daily, IV Ceftriaxone 1g twice daily, IV Ciprofloxacin 400mg twice daily, PO Propranolol 40mg three times daily with a target heart rate <90 beats per minute, and PO Thiamazole 5mg once daily initiation again because there is no side efect at previous medication with the same regiment and the alternative treatment such as iodine radioactive and surgery did not perform yet. Although initially the ANC was low, the patient's condition improved, and she was discharged after 13 days of treatment with normal laboratory results. Follow-up outpatient monitoring showed continued improvement. Accurate diagnosis and appropriate management are crucial in handling agranulocytosis induced by antithyroid drugs, which can significantly improve treatment outcomes and the patient's prognosis.